Amanda joins the circus - Avi, 1937-; Wisniewski, David (New York, N.Y. : Avon Books, 1998)
Amanda the racoon wants to join a circus as a clown.
"As seen in newspapers nationwide"--Cover.
4.9.
4.9
3-6
Keywords: Animals -- Fiction; Circus animals -- Fiction; Circus -- Fiction; Clowns -- Fiction; Animals -- Fiction; Circus animals -- Fiction; Circus -- Fiction; Clowns -- Fiction